Retroperitoneal bleeding caused by spontaneus rupture of renal angiomyolipoma following cesarean section treated with selective embolisation - Harašta, J; Huml, K (Ceska gynekologie, 2019)
OBJECTIVE: To describe management of a spontaneus rupture of renal angiomyolipoma after cesarean section. DESIGN: Case report. SETTING: Department of Gynaecology and Obstetrics, Hospital Šternbek; Department of Obstetrics and Gynaecology, Palacky University and University Hospital, Olomouc. CASE REPORT: 29-year-old patient underwent acute cesarean section at 35 weeks of gestation for pPROM, placenta praevia marginalis, suspicion of placenta accreta by ultrasound and MRI and transverse position of the fetus. The next morning was found out a spontaneus rupture of renal angiomyolipoma causing progressive anemisation. We describe the following management. CONCLUSION: Incidention of tumors complicating gravidity may occur more often due to changes in population characteristics. Methods of interventional radiology are ordinarily used for severe hemorrage postpartum or for prophylactic occlusion of illiac arteries before cesarean section with morbidly adherent placenta. We show here usage of selective embolisation in not so common obstetrical complications.
Keywords: placenta praevia; tamponade; Cesarean Section; placenta accreta; těhotenství; Placenta Previa; cesarean section; krvácení; embolisation; Adult; císařský řez; puerperium; ženské pohlaví; angiomyolipom; bleeding; Humans; Pregnancy; Hemorrhage; Placenta Accreta; dospělí; angiomyolipoma; Female; lidé; Angiomyolipoma